Natural Space and Social Space of Community Interaction in the Dynamics of Tourism Economy - Nasehudin, Nasehudin; Ya’afi, Najmi Khalifatan; Cholid, Budi Akung; Sholehudin, Azis (Transpublika Publisher, 2025)
This research aims to examine how natural and social spaces are interpreted and managed by the people of Paniis Village, Kuningan Regency, within the framework of community-based tourism economic development. Using a descriptive qualitative approach, this research was conducted through participatory observation, in-depth interviews, and field documentation. The findings show that the development of village tourism has encouraged significant social transformation, ranging from changes in economic patterns, shifts in social identity, to the emergence of new forms of community collaboration. The utilisation of potential natural spaces such as waterfalls and mountain landscapes not only brings economic benefits, but also forms an arena for social interaction and local cultural expression. However, challenges such as unequal access to benefits, cultural commodification, and ecological pressure are important issues that need to be managed collectively. In conclusion, tourism in Paniis Village is not only an economic practice, but also a space for the production of values, solidarity, and identity that can be a model of community-based sustainable development.